Horizontes y desafíos de descolonización en Bolivia (Tema Central) - Saavedra, José Luis (2006)
The author conducts an approach to the context of the socio-state and governmental experience that is beginning to be felt in Bolivia and whose public policies, at least the most important, are beginning to be designed from the perspective of decoloniality. This theoretical and political horizon plants a series of possibilities as well as challenges. The article intent is to elucidate these emergent experiences, their risks and challenges.